An Analysis of Orthopedists and Physiatrists’ Perceptions of Organizational Culture, Organizational Commitment and Leadership In Terms of Some Variables, - Korkmaz, M., Kılıç, B., Yücel, A. S., Aksoy, M. (My University, 2014)
Background: To establish an efficient organizational culture and leadership is of main importance for a high quality service in the hospitals. Organizational culture, organizational commitment, decision making process, and the mission and vision of the corporation, and the efficient leadership behaviors are among the topics that have been emphasized recently. It is worth analyzing the perceptions of Orthopedists and Physiatrists about organizational culture, organizational commitment and leadership in order to maintain service quality, organizational culture and performance and to take necessary precautions. Objective: The purpose of the study is to examine the Orthopedists and Physiatrists? perceptions of organizational culture, organizational commitment and decision making process and leadership definitions in terms of some variables. In this respect, a questionnaire has been prepared for 860 participants. Data obtained from the participants have been analyzed with PASW Statistics 18 package programme. Cronbach's Alpha coefficient was 0.962 at the end of the reliability analysis. Data obtained from the study have been analyzed with descriptive statistics, reliability analysis, chi square, ANOVA, Duncan, Man-Whitney-U, Kruskal Wallis, Wilcoxon, Kolmogorov-Smirnov-Z tests. Results: it has been observed that, the position in the corporation and educational factors differentiate in the items concerning the organizational culture, and the leadership definitions differ according to gender, age, marital status, and education. Conclusion: At the end of the study, There is a difference between hospital commitment and age, the vision and the mission of the corporation, and gender and education. Further to this, perceptions of the leadership differ according to gender.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Organizational Culture; Organizational Commitment; Hospital; Leadership